2016
DOI: 10.1093/jxb/erw174
|View full text |Cite
|
Sign up to set email alerts
|

The role of transketolase and octulose in the resurrection plantCraterostigma plantagineum

Abstract: HighlightTransketolase 7 and 10 of Craterostigma plantagineum participate in the synthesis of octulose phosphate in an alternative Calvin cycle. Octulose is the main transport sugar in fully hydrated plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Craterostigma and L. brevidens accumulate the unusual C8 sugar 2-octulose in photosynthetic tissues, which serves as a reservoir of sucrose accumulation during desiccation (Bianchi et al, 1991;Phillips et al, 2008). Transketolase7 and -10 catalyze the formation of octulose-8-phosphate in Craterostigma (Zhang et al, 2016), and the orthologous transketolase genes were highly expressed in L. brevidens leaf tissue ( Supplemental Table 10). This included two pairs of syntenic 1:1 orthologs and a trio of retained 2:1 duplicates, with upregulation in well-watered and rehydrating tissue in L. brevidens and no or little expression in L. subracemosa.…”
Section: Unique Desiccation-related Pathways In L Brevidensmentioning
confidence: 99%
“…Craterostigma and L. brevidens accumulate the unusual C8 sugar 2-octulose in photosynthetic tissues, which serves as a reservoir of sucrose accumulation during desiccation (Bianchi et al, 1991;Phillips et al, 2008). Transketolase7 and -10 catalyze the formation of octulose-8-phosphate in Craterostigma (Zhang et al, 2016), and the orthologous transketolase genes were highly expressed in L. brevidens leaf tissue ( Supplemental Table 10). This included two pairs of syntenic 1:1 orthologs and a trio of retained 2:1 duplicates, with upregulation in well-watered and rehydrating tissue in L. brevidens and no or little expression in L. subracemosa.…”
Section: Unique Desiccation-related Pathways In L Brevidensmentioning
confidence: 99%
“…Thus, only further identification of the cellular localization and properties of enzymes with multiple roles can help to understand the contribution of these enzymes to desiccation tolerance. The studies on transketolase of C. plantagineum from Bernacchia et al (1995), Willige et al (2009), and Zhang et al (2016) provide an example for this proposal: three isoforms of transketolase (tkt3, tkt7, and tkt10) have been characterized on the molecular level in C. plantagineum ; tkt3 is localized in chloroplasts while tkt7 and tkt10 are localized in the cytoplasm; tkt3 is suggested to be involved in carbon reactions in photosynthesis and the pentose phosphate pathway, while tkt7 and tkt10 are involved in the accumulation of octulose in C. plantagineum [67,68,69]. …”
Section: Sugar Metabolism During Dehydration Studied By Proteomicsmentioning
confidence: 99%
“…Octulose in Craterostigma species may have a similar role as starch in providing carbon resources for sucrose or RFOs synthesis [26,70]. Zhang et al (2016) demonstrated that C. plantagineum tkt7 and tkt10 catalyze the synthesis of octulose-8-phosphate using glucose-6-phosphate and fructose-6-phosphate as substrates [69]. Besides starch degradation, dehydration also induces alterations of the polysaccharide contents and structure in the cell wall of resurrection plants [75].…”
Section: The Relationships Among Sugar Accumulation Energy Metabomentioning
confidence: 99%
See 1 more Smart Citation
“…The enzyme transketolase is a limiting factor of photosynthesis, and small changes in its activity can lead to the inhibition of plant growth as well as phenylalanine and aromatic amino acid metabolism [ 3 , 4 , 5 , 6 ]. Since transketolase plays a key role in plant photosynthesis, and is highly conserved in plants, it represents an important candidate target for the development of new herbicides.…”
Section: Introductionmentioning
confidence: 99%